Barriers and Catalysts of Entrepreneurial Success in the Hospitality Industry: A Mixed-Method Analysis (PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: The hospitality sector, a significant global economic driver, faces numerous challenges including regulatory hurdles, financial constraints and workforce shortages, particularly in developing economies like India. Understanding the factors influencing entrepreneurial success in this sector is crucial for fostering sustainable growth. Objectives: This study aims to identify key barriers and catalysts affecting entrepreneurial activities in the hospitality industry and to analyse the internal factors such as entrepreneur’s diverse socio-economic and professional backgrounds that influences their journey and growth. Methodology: A mixed-method approach was employed, combining quantitative and qualitative data collection. An online survey with 11 closed-ended questions was distributed to 150 entrepreneurs in Mumbai and surrounding areas, resulting in 82 responses (55% response rate). Data collection technique used was convenience sampling. Additionally, in-depth interviews were conducted with 10 selected entrepreneurs. Quantitative data was analysed using descriptive statistics, while qualitative data was analysed through thematic analysis. Results: The study revealed that middle-level professionals with family business backgrounds are key drivers of entrepreneurship. 83% of respondents planned business expansion, with scalable ventures like cafes and food outlets being preferred due to lower capital requirements. 89% of respondents agreed that small businesses significantly enhance tourism. 63% agreed that management education develops business skills, but only a minority believed it adequately fosters creativity and innovation. 84% of respondents were flexible to relocate for business. Conclusion: The research highlights the critical role of family background, practical experience and adaptability in entrepreneurial success within the hospitality industry. While management education provides foundational skills, there is a need for enhanced focus on creativity and innovation. Government support, financial accessibility and infrastructure development are essential to mitigate barriers and foster a resilient entrepreneurial ecosystem.
Keywords: Entrepreneurs; hospitality; entrepreneurial barriers; government incentives; workforce challenge